EVALUASI EFEKTIVITAS PENERIMAAN PENDAPATAN RETRIBUSI PASAR DI DINAS KOPERASI DAN UKM KABUPATEN MINAHASA TENGGARA - Rantetadung, Romario; Ilat, Ventje; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Regional autonomy is regional empowerment in regional decision making that is more flexible to manage the resources possessed with the potential and interests of the region itself. Errors that make natural resources as the main factor in the source of regional income must be immediately changed because one day natural resources will be exhausted. The purpose of this study is to find out the process of Receiving Market Retribution in the Southeast Minahasa District Cooperative and SME Service and the effectiveness of Retribution Income at the Southeast Minahasa Regency Cooperative and SME Office. The analytical method used is descriptive qualitative. The results of the study show that the evaluation of the effectiveness of market retribution revenue at the Minahasa Regency Cooperative and SME Office in North Sumatra is quite effective. the advice given is to increase the process of collecting and depositing market retribution in the Southeast Minahasa District Government and for the Southeast Minahasa Regency government to pay more attention to the regulations issued so that the Effectiveness of Market Levy Income Revenues can achieve maximum results.